Pengaruh Budaya Perusahaan dan Komitmen Perusahaan terhadap Intensitas Peran Akuntansi Manajemen. Studi Kasus Perusahaan Manufaktur di Bogor - Nurjanah, Yayuk (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2010)
The Purpose of this research is to find out and to analyze (1) the influence of corporate culture to the role intensity of management accounting; (2) the influence of corporate commitment to the role intensity of management accounting; (3) the influence of corporate culture and corporate commitment simultaneously to the role intensity of management accounting. Research type is hypothetical test research. Research population is manufacture firm, and the samples are manager at manufacture firms in Bogor. Data collecting method by questionaire via post as many as 100 copies, to be send back as many as 52 copies (52%), and 45 copies (45%) can be processed. Statistical test is data quality test, classical assumption, and hypothetical test. The analysis result are (1) corporate culture has significant influence to the role intensity of management accounting; (2) corporate commitment has significant influence to the role intensity of management accounting; (3) corporate culture and corporate commitment simultaneously have significant influence to the role intensity of management accounting. Keywords: Corporate culture, Corporate Commitment, Role Intensity Of Management Accounting